2019
DOI: 10.1093/ije/dyz190
|View full text |Cite
|
Sign up to set email alerts
|

Appraising the causal relevance of DNA methylation for risk of lung cancer

Abstract: BackgroundDNA methylation changes in peripheral blood have recently been identified in relation to lung cancer risk. Some of these changes have been suggested to mediate part of the effect of smoking on lung cancer. However, limitations with conventional mediation analyses mean that the causal nature of these methylation changes has yet to be fully elucidated.MethodsWe first performed a meta-analysis of four epigenome-wide association studies (EWAS) of lung cancer (918 cases, 918 controls). Next, we conducted … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 41 publications
2
54
0
Order By: Relevance
“…Our results, hence, do not support the hypothesis that smoking‐induced methylation changes mediate the effect of smoking on lung cancer risk. Similar conclusions were reached in a recent two‐step Mendelian randomization analysis …”
Section: Data Application: Smoking Dna Methylation and Lung Cancer supporting
confidence: 88%
“…Our results, hence, do not support the hypothesis that smoking‐induced methylation changes mediate the effect of smoking on lung cancer risk. Similar conclusions were reached in a recent two‐step Mendelian randomization analysis …”
Section: Data Application: Smoking Dna Methylation and Lung Cancer supporting
confidence: 88%
“…7 However, we found in MR analysis that there was no strong evidence for a causal effect of AHRR methylation on FEV 1 , indicating that it is unlikely to be mediating the effect of smoking on lung function. Similar conflicting findings have been observed between conventional mediation approaches and MR analysis aimed at determining epigenetic mediation in the context of smoking and lung cancer 49,50 and of prenatal famine and later-life metabolic profile. 51,52 Traditional mediation approaches are more susceptible to measurement error and potential reverse causation than MR, 53 meaning the proportion of the mediated effect reported by these studies is likely to be overestimated.…”
Section: Comparison With Other Studiesmentioning
confidence: 55%
“…In the population-based study by Bojesen et al of approximately 23% never smokers and current/former smokers with mean smoking histories of fewer than 40 pack years, an over four-fold increased risk of lung cancer for individuals in the lowest versus highest methylation quintiles (95% CI: 2.31–10.30) was observed after adjusting for smoking status, cigarettes per day, and pack years [ 9 ]. In four publications reporting on combinations of study populations from up to five nested case-control studies, with each individual nested case-control study comprised of 63 to 367 pairs, statistically significant 40–60% increased risks of lung cancer per standard deviation decrease in cg05575921 methylation were reported [ 4 , 19 , 21 , 22 ]. These results maintained statistical significance after adjustment for smoking for all but one study, which reported a statistically significant 63% increased risk that was attenuated and no longer statistically significant after controlling for smoking features (e.g., smoking status, pack years, comprehensive smoking index) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%